Identifikasi Bakteri pada Produk Keripik Kelapa Bulian (Cocos Nucifera L.) dengan Metode Kultur dan Pewarnaan Gram - Lulu Wafiq Wafizo; Ardi Mustakim (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Bulian coconut chips are a typical Jambi food made from dried and fried old coconuts. The traditional production method and inadequate hygiene standards make this product susceptible to microbial contamination, especially harmful bacteria. This study aims to identify the types of bacteria that may be present in Bulian coconut chips using culture and Gram staining methods as the initial step for morphological identification. Samples were taken from three local producers in Bulian District, Batanghari Regency, Jambi. Testing was carried out by serial dilutions up to 10⁻⁴, then planted on Nutrient Agar (NA) media and incubated for 24 hours at 37°C. The colonies that grew were then observed morphologically and Gram staining was performed using a modified method without alcohol. The results showed the presence of various colonies with cream, white, and pale yellow colors. Based on the results of Gram staining, bacilli and cocci were found, which were included in the Gram-positive and Gram-negative categories. The types of bacteria suspected to appear include Bacillus sp., Staphylococcus sp., and possibly Escherichia coli. These findings indicate a risk of microbial contamination that could endanger consumer health, especially if the production process is not improved. Strict hygiene and sanitation principles are strongly recommended in the processing of this traditional food to ensure the product remains safe for consumption. The importance of implementing hygienic standards in the production of Bulian coconut chips is further emphasized by these findings. In addition to improving food safety, implementing proper sanitation procedures can also extend the product's shelf life and increase consumer confidence in local traditional foods. Efforts such as training local producers, using clean equipment, and hygienic packaging can help minimize the risk of bacterial contamination.